2007
DOI: 10.5194/osd-4-107-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling aspects of the sea-ice-drift dynamics and pack fracture

Abstract: Abstract. A study of the sea-ice dynamics in the periods of time prior to and during the cycles of basin-wide fragmentation of the ice cover in the Arctic Ocean is presented. The fractal geometry of the ice-sheets limited by leads and ridges was assessed using the satellite images, while the data on the correlated sea-ice motion were obtained in the research stations "North Pole 32" and "North Pole 33" established on the ice pack. The revealed decrease of the fractal dimension as a result of large-scale fragme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There were reported previously (Chmel et al, 2005(Chmel et al, , 2007 some time characteristics of the sea ice drift in the Arctic Ocean as revealed from the field observations that were carried out at the research station "North Pole 32" (NP 32) established on the ice pack in [2003][2004]. The sequences of events of accelerations of an individual ice field were found to be self-similar (or, in terms of the critical dynamics, fractal) during quasi-stationary periods of drift and fully disordered (truly random) when the great pack fragmentation occurred in the region of the NP 32 activity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…There were reported previously (Chmel et al, 2005(Chmel et al, , 2007 some time characteristics of the sea ice drift in the Arctic Ocean as revealed from the field observations that were carried out at the research station "North Pole 32" (NP 32) established on the ice pack in [2003][2004]. The sequences of events of accelerations of an individual ice field were found to be self-similar (or, in terms of the critical dynamics, fractal) during quasi-stationary periods of drift and fully disordered (truly random) when the great pack fragmentation occurred in the region of the NP 32 activity.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies of the sea ice drift and mechanical behavior of the ice pack, including its deformations and fragmentations, revealed that the Arctic sea ice cover (ASIC) exhibits well-pronounced scaling properties typical for the dynamics of the non-equilibrium, permanently critical systems (Marsan et al, 2004;Korsnes et al, 2004;Smirnov et al, 2006;Chmel et al, 2007;Rampal et al, 2008). The spatial, energy and temporal distributions of the mechanical events in the ASIC follow the power law with varying exponents thus indicating the existence of a latent relationship between the scaling features and underlying physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…e data on the local dri dynamics were collected in the Russian ice research camp North Pole 32 (NP 32) that was established on ice pack and dried in [2003][2004] in the region north from Franz Josef Land from 88 ∘ N to 84 ∘ N [8]. In this work, the time series of the kinetic energy variation of an individual ice �oe were analyzed using the Tsallis statistics in order to obtain a thermodynamic characteristic of the system of driing ice prior to and during large-scale sea ice fragmentations.…”
Section: Introductionmentioning
confidence: 99%